Lichen Biota Of The Wolin Island (Poland) - Wieczorek, Anetta; Łysko, Andrzej (Biodiversity: Research and Conservation, 2012)
A list of 232 taxa of lichenized and lichenicolous fungi was recorded within the Wolin island, especially, the Wolin National Park. The findings comprise the results of field studies conducted between 1996 and 2008 and those published in earlier works. Some of them are rare in the Polish lowlands.